2019
DOI: 10.1007/s12144-018-0120-4
|View full text |Cite
|
Sign up to set email alerts
|

A clash of constructs? Re-examining grit in light of academic buoyancy and future time perspective

Abstract: A very special thanks to Dr. Carlton J. Fong who was with me from the start of the master program. His encouragement, recommendations, creativity, sense of humor, and patience helped me have a strong interest in this area and complete this thesis and my degree. I also thank my parents who have loved and supported me unconditionally. I will always be indebted to them, and I appreciate everything that they have done for me.Without their assistance and support, I would have never finished my thesis. Thank you for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 64 publications
1
24
1
5
Order By: Relevance
“…There is a growing body of evidence on academic buoyancy, traversing: (1) research differentiating buoyancy from other constructs (e.g., from coping, adaptability, grit, control, anxiety, and academic fear; Fong & Kim, 2019; Martin, Nejad, Colmar, & Liem, 2013; Putwain & Aveyard, 2018; Putwain, Chamberlain, Daly, & Sadreddini, 2014; Putwain, Daly, Chamberlain, & Sadreddini, 2015; Putwain et al, 2012; Putwain & Daly, 2013; Putwain et al, 2015; Symes, Putwain, & Remedios, 2015); (2) research on predictors of academic buoyancy (e.g., motivation predictors; Collie, Martin, Malmberg, Hall, & Ginns, 2015; Martin, Colmar, Davey, & Marsh, 2010; Martin & Marsh, 2006); (3) research on outcomes predicted by academic buoyancy (e.g., engagement; Martin, 2013; Martin & Marsh, 2008a); (4) intervention research targeting buoyancy (e.g., Puolakanaho et al, 2019; Putwain, Gallard, & Beaumont, 2019); and (5) research into buoyancy among different samples and contexts (e.g., cross-cultural comparisons; Collie et al, 2017; Datu & Yang, 2018; Martin, Yu, Ginns, & Papworth, 2017; Yun, Hiver, & Al-Hoorie, 2018).…”
Section: Academic Buoyancymentioning
confidence: 99%
“…There is a growing body of evidence on academic buoyancy, traversing: (1) research differentiating buoyancy from other constructs (e.g., from coping, adaptability, grit, control, anxiety, and academic fear; Fong & Kim, 2019; Martin, Nejad, Colmar, & Liem, 2013; Putwain & Aveyard, 2018; Putwain, Chamberlain, Daly, & Sadreddini, 2014; Putwain, Daly, Chamberlain, & Sadreddini, 2015; Putwain et al, 2012; Putwain & Daly, 2013; Putwain et al, 2015; Symes, Putwain, & Remedios, 2015); (2) research on predictors of academic buoyancy (e.g., motivation predictors; Collie, Martin, Malmberg, Hall, & Ginns, 2015; Martin, Colmar, Davey, & Marsh, 2010; Martin & Marsh, 2006); (3) research on outcomes predicted by academic buoyancy (e.g., engagement; Martin, 2013; Martin & Marsh, 2008a); (4) intervention research targeting buoyancy (e.g., Puolakanaho et al, 2019; Putwain, Gallard, & Beaumont, 2019); and (5) research into buoyancy among different samples and contexts (e.g., cross-cultural comparisons; Collie et al, 2017; Datu & Yang, 2018; Martin, Yu, Ginns, & Papworth, 2017; Yun, Hiver, & Al-Hoorie, 2018).…”
Section: Academic Buoyancymentioning
confidence: 99%
“…Although the bivariate correlations in these studies (Collie et al, 2015;Fong & Kim, 2019;Putwain & Aveyard, 2018) were positive (rs ϭ .10 to .15), in the presence of related variables the predictive value of academic buoyancy was reduced. This reduction of direct effects may be attributable to the effects of buoyancy being mediated by other variables (e.g., buoyancy bolstering perceived control, and control influencing performance in the studies by Collie et al, 2015, andAveyard, 2018).…”
Section: What Is It and How Does It Differ From Cognate Constructs?mentioning
confidence: 65%
“…In studies of secondary school students that have included control, academic buoyancy did not predict academic achievement on standardized school numeracy and literacy tests (Collie, Martin, Malmberg, Hall, & Ginns, 2015) or secondary school exit examinations in English, mathematics, and science (Putwain & Aveyard, 2018). In the aforementioned study by Fong and Kim (2019), academic buoyancy was not significantly related with self-reported GPA in undergraduates after controlling for grit and future time perspective.…”
Section: What Is It and How Does It Differ From Cognate Constructs?mentioning
confidence: 78%
See 1 more Smart Citation
“…Academic buoyancy has not only been differentiated from academic resilience but also from cognate constructs including grit (persistency of effort and consistency of interest; Duckworth, Peterson, Matthews, & Kelly, 2007), future time perspective (the perceived connection between present activities and future goals; Lens & Seginer, 2015), and coping (efforts to regulate emotion and behaviour under stressful conditions; Skinner & Saxon, 2019). Using a principal components analysis, Fong and Kim (2019) showed that academic buoyancy, grit, and future time perspective, items loaded onto their target factors with no cross-loading items (λs > .35). In relation to coping, academic buoyancy has been shown small to negligible correlations (rs = -.13 to .08) with adaptive forms of coping, such as taskfocus and seeking help, and maladaptive forms of coping, such as avoidance (Putwain, Connors, Symes, & Douglas-Osborn, 2012;Putwain et al, 2016).…”
Section: Academic Buoyancy: What Is It and What Is It Not?mentioning
confidence: 99%